Estabelecimento de um critério de sucesso para avaliação da efetividade de intervenções multiprofissionais para o tratamento da obesidade em adolescentes - Bianchini, Josiane Aparecida Alves (2016)
The current scenario of Brazil in relation to the prevalence of overweight in children and adolescents is worrisome. Thus, the implementation of interventions for the treatment of obesity and its comorbidities are urgently needed to control the situation and improving children's and adolescents' health. The multidisciplinary interventions are among the options that have shown significant results in relation to several health-related parameters on youths. However, it seems to be a consensus in the literature as to which would be the most important parameter for monitoring the effects of these types of interventions. To assess the impact of the gain / maintenance or weight loss on the effects of a PMTO, assess the impact of the degree of change on Z score of BMI on changes in HRQoL of adolescents who completed a PMTO and propose a success criterion to analyze the effectiveness of a multidisciplinary program of obesity treatment in adolescents (PMTO). They were part of the 169 teenagers data analysis of both sexes (103 in the intervention group (GI) and 66 in the control group (CG)), with a median age of 12 (11-14) years (GI) and 13 (12 - 14) years (GC), who participated for 16 weeks of PMTO-NEMO-UEM between the years 2009 to 2013. The interventions were carried out three times a week, on Mondays, Wednesdays and Fridays from 16:00 to 18:00, conducted by a team of professionals and students of physical education, nutrition and psychology. We collected anthropometric data, body composition, cardiorespiratory fitness, HRQOL, biochemical and hemodynamic parameters and sexual maturation. To establish the success criteria variables were included: 1) Total domain of HRQOL; 2) Z score of BMI; 3) VO2max; 4) Body weight; 5) Waist circumference (WC); 6) Fat Mass and 7) Lean mass. The percentage changes of each of the seven parameters involved were observed. Those with negative change in expected reduction during the intervention (Z score of BMI, body weight, fat mass and WC) were multiplied by "-1" to conversion into positive values and obtain the scores of the success criteria for proposals from the sum between parameters. The adolescents GI who lost weight showed improvements in maximal oxygen uptake (23.54 ± 5.30 mL / kg / min to 25.39 ± 5.63 mL / kg / min), relative fat (49.29 ± 6.98% to 46.75 ± 8.56%), triglyceride levels (116.58 ± 46.50 mg / dL to 101.19 ± 43.08 mg / dL), diastolic blood pressure (75.81 mmHg ± 8.08 71.19 ± 6.34 mmHg) and number of risk factors for metabolic syndrome (2.00 ± 1.06 to 1.58 ± 1.10). Teenagers of the GOI which gained / maintained their weight decreased in relative fat (48.81 ± 5.04% to 46.60 ± 5.53%), systolic blood pressure (123.39 ± 14.58 mmHg to 115, 83 ± 7.02 mmHg), diastolic blood pressure (74.83 ± 9.91 mm Hg to 68.78 ± 5.95 mmHg), number of risk factors for metabolic syndrome (1.67 ± 1.09 to 1.11 ± 0.68), lean body mass (39.00 ± 7.20 kg to 7.53 kg ± 41.85) and the maximal oxygen uptake (23.74 ± 4.40 mL / kg / min for 25 29 ± 5.17 ml / kg / min) increased similarly to adolescents who lost weight. Adolescents who showed change <0.25 in BMI z score improved the physical domain (78.5 ± 13.5 vs 84.1 ± 9.9) and the total (75.1 ± 12.9 vs 78.1 ± 11.4) of HRQOL as well as teens who had <0,25 change in Z score of BMI (Physical: 75.8 ± 16.0 vs 81.4 ± 14.1; total: 73.4 ± 16, 1 vs. 78.2 ± 12.8). There were four different proposals in which adolescents can be classified after completing this intervention model: 1) percentile values GC 50 or lower are considered non-responsive to intervention; 2) Amounts exceeding GC 50th percentile but below the 50th percentile GI are considered somewhat responsive to intervention; 3) GI percentile values above 50 but below 75 GI percentile were considered as moderately responsive to intervention; 4) Values greater than 75th percentile GI were considered very responsive to intervention. Sixteen weeks of PMTO promoted positive change in body composition and cardiometabolic risk factors, irrespective of changes in weight. Changes in BMI z score did not influence changes in HRQoL sobrepesados obese adolescents and followed in a multidisciplinary intervention. It is believed that the proposed criteria of success may be used as an additional tool for monitoring the response to a multidisciplinary intervention program.